2012
DOI: 10.5005/jp-journals-10025-1003
|View full text |Cite
|
Sign up to set email alerts
|

Refractive, Tomographic and Biomechanical Outcomes after Implantation of Ferrara ICRS in Keratoconus Patients

Abstract: Background: Nowadays, ICRS are a step in the treatment of keratoconus. The purpose of this study was to evaluate the refractive effect and the tomographic and biomechanical parameters in keratoconus patients implanted with Ferrara ICRS, and their stability after 18 months. Materials and methods:Twenty eyes of 20 keratoconus patients implanted with ICRS were evaluated. The average follow-up was 18 months. UDVA, CDVA, biomicroscopy, tomography (Pentacam) and biomechanics (ORA) of the cornea were evaluated before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the other hand, the current study revealed a decrease in the apex and at the thinnest point, as well as a decrease in the maximum elevation inside the 4-mm zone. Sögütlü et al 2 and Salgado-Borges et al 13 found similar results.…”
Section: Relationship Between Tomographic Parameters and Visual Outcomesmentioning
confidence: 63%
See 2 more Smart Citations
“…On the other hand, the current study revealed a decrease in the apex and at the thinnest point, as well as a decrease in the maximum elevation inside the 4-mm zone. Sögütlü et al 2 and Salgado-Borges et al 13 found similar results.…”
Section: Relationship Between Tomographic Parameters and Visual Outcomesmentioning
confidence: 63%
“…Average K readings decreased from 51.83 ± 6.87 to 47.66 ± 6.08 D (P < .001). Rho et al, 1 Söglütü et al, 2 and Salgado-Borges et al 13 found similar postoperative results: 51.80 ± 4.68 to 49.59 ± 3.71 (P < .001), 50.94 ± 5.01 to 47.78 ± 4.00 (P < .01), and 50.7 ± 4.2 to 47.5 ± 3.7 (P = .0003) D, respectively. We found a decrease from 48.6295 ± 4.2837 D preoperatively to 46.3882 ± 3.6654 D postoperatively (P < .0001).…”
Section: Relationship Between Tomographic Parameters and Visual Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were found in CH in the short-term (<3rd month) postoperative period [ 104 106 ] which may indicate that the ICRS alter corneal curvature without changing the viscoelastic response of the corneal tissue. A study conducted on 20 patients with keratoconus showed a stable corneal flattening and a decrease of the astigmatism with no statistically significant changes in ORA parameters, 18 months after ICRS implantation [ 107 ]. Better visual outcomes could be expected for corneas with lower biomechanical corneal resistance due to easier deformation by the ring implantation.…”
Section: Factors Affecting Corneal Biomechanical Propertiesmentioning
confidence: 99%
“…[14][15][16][17] Recent studies have reported their effective use for the treatment of keratoconus and ectasia resulting from keratorefractive surgery. 18 Treatment with intrastromal rings does not eliminate the progression of keratoconus, but it may delay a corneal transplant procedure.…”
Section: Introductionmentioning
confidence: 99%